Proposed interior design of Asiatica Palace Morrocan Restaurant at Jalan Sultan Badlishah,05000 Alor Setar, Kedah for Asiatica Palace of Middle East Cuisine (M) Sdn. Bhd / Nurul Asyikin Kamarudin - Kamarudin, Nurul Asyikin (Faculty of Architecture, Planning and Surveying, 2012)
This project is about Proposed Interior Design Of Asiatics Palace Morrocan Restaurant at Jalan Sultan Badlishah,05000 Alor Setar, Kedah For Asiatica Palace Of Middle East Cuisine (M) Sdn. Bhd. The total interior area is 4352 sq. ft. This area is very strategic to run business in food such as open a new branch of Asiatica Palace Morrocan Restaurant, cafe or other cafeteria. The main target are the visitor and the surounding people also for surrounding workers and citizen at shop lot area. It was at a centre of Alor Setar city area. This area also a centre for investment activities, marketing, educational, officer and social activity area. Besides that this location provide many facility such as public transport (bus and taxi),bank,bus stop and petrol station. This project is to introduce a new branch of Asiatica Palace Morrocan Restaurant in a centre of Alor Setar, Kedah and at the same time to create a systematic flow complete to make comfort for customer to get the services. Besides that to exist a surrounding of middle east culture and cuisine especially in Moroccan style. Style of the interior for this restaurant is Moroccan style since that Moroccan is a part of middle east.